Glycaemic Status in Acute Stroke in Nondiabetic Patient (Journal of Medicine, 2021)
Background: Elevated blood glucose is common in the early stage of stroke. Besides, blood glucose level increases during acute stroke in nondiabetic patients.Objective: Objective of the study was to assess the glycemic status during acute stroke in nondiabetic patients, find the rate of newly developed diabetes during acute stroke and rate of newly developed Impaired Fasting Glucose, Impaired Glucose Tolerance during acute stroke.Methods: The purposive sampling method was used to identify the patients and by proper history taking, documentary papers and laboratorial support evidenced by HbA1c level less than 6.5% (This means patient to be non diabetic). Data were collected from 100 patients. It was conducted from August, 2018 to February, 2019 in the Department of Medicine of Dhaka Medical College Hospital. The data were collected through questionnaire ,pre-tested earlier and data collection sheet illustrating the glycemic status during acute stroke among the nondiabetic patients.Results: While analyzing the lab investigations among the respondents, mean HbA1c level was found 5.69± 0.65 mmol/L level which was found normal among the entire patient group. Patients Fasting Blood Sugar(FBS) was tested and mean FBS level was 5.94±0.86. In 62% of the patients, IFG was found, and in 12% of patients, FBS value was found to be diabetic while 26% showed normal glycemic status. Average OGTT(2 hours after 75 gm glucose) impression was 8.53± 2.02 mmol/L. OGTT level was normal among 30%, 54% patients had IGT and 16% of the respondents were found diabetic.Conclusion: The study finds that, in patients with no history of diabetes who have acute stroke, may develop moderately elevated glucose levels which may affect short term and long term stroke related morbidity and mortality.J MEDICINE JAN 2021; 22 (1) : 22-26